If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c = 7(y + k) Reorder the terms: c = 7(k + y) c = (k * 7 + y * 7) c = (7k + 7y) Solving c = 7k + 7y Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Simplifying c = 7k + 7y
| 7+m=7(1-6m) | | 2.86x+14.3=28.6 | | 7(y+k)=c | | -5(-9-3x)=21 | | 6+(4h+3)= | | x-7=(6x-12) | | 3X-5=2(X+3)-11 | | 4-5=t | | 4a^2=-4a-5 | | z+2y-4= | | 3x+25=30+3-12 | | (15+6x)=36 | | 2(u-1)-3u=(u-6) | | 7.7(x-2)=-.3x+48.6 | | -20+x=x+9 | | 4y-16=-6(y+1) | | 5(x-2)-7=-6 | | ln(6x)=13 | | 1.1-49t=.3 | | 1.1-49t=1.1 | | 6+44=-5(7x-10) | | 4f-2f+3= | | 3(4x+9)=5(2x-5) | | 1.1=1.1-49t | | 4(-k-8)=3k-39 | | -7=5+3u | | 3(y-8)=3+2y | | -2(4-4x)=-40+4x | | 10n-6=14 | | 229=12-x | | 7(-a+8)=2a+2 | | -2u=-32 |